2020
DOI: 10.1002/chem.202004555
|View full text |Cite
|
Sign up to set email alerts
|

Silicon–Nitrogen Bond Formation via Heterodehydrocoupling and Catalytic N‐Silylation

Abstract: Silicon–nitrogen bond formation is an important subfield in main group chemistry, and catalysis is an attractive route for efficient, selective formation of these bonds. Indeed, heterodehydrocoupling and N‐silylation offer facile methods for the synthesis of small molecules through the coupling of primary, secondary, and tertiary silanes with N‐containing substrates such as amines, carbazoles, indoles, and pyrroles. However, the reactivity of these catalytic systems is far from uniform, and critical issues are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 81 publications
2
38
1
Order By: Relevance
“…Well-defined organometallic complexes have played a key role in the development of catalytic cross-couplings, with hetero­dehydrocoupling of protic X−H and hydridic Y–H fragments advocated as a particularly attractive and atom-economical route to the generation of X−Y bonds (Scheme a). ,, A generalized mechanism for processes catalyzed by redox-inactive d 0 metal centers may be envisaged as a defined sequence of M−X/Y–H metathesis events to provide the new X−Y bond and an intermediate metal hydride, which is subsequently protonated by the protic X−H function to regenerate the M−X species through the elimination of H 2 (Scheme b). While the initial focus of research derived from alkaline metal species was centered on the use of Group 2 species, sporadic studies of superficially similar Group 1-based catalysis have also emerged during the last decade.…”
Section: Molecular Hydrides Of the Group 1 Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Well-defined organometallic complexes have played a key role in the development of catalytic cross-couplings, with hetero­dehydrocoupling of protic X−H and hydridic Y–H fragments advocated as a particularly attractive and atom-economical route to the generation of X−Y bonds (Scheme a). ,, A generalized mechanism for processes catalyzed by redox-inactive d 0 metal centers may be envisaged as a defined sequence of M−X/Y–H metathesis events to provide the new X−Y bond and an intermediate metal hydride, which is subsequently protonated by the protic X−H function to regenerate the M−X species through the elimination of H 2 (Scheme b). While the initial focus of research derived from alkaline metal species was centered on the use of Group 2 species, sporadic studies of superficially similar Group 1-based catalysis have also emerged during the last decade.…”
Section: Molecular Hydrides Of the Group 1 Metalsmentioning
confidence: 99%
“…281,346 While attempted boron−boron bond activation of the diborane, B 2 pin 2 provided similar quaternization of boron, both hydrides of the dimeric compound 113 were observed to add to a single boron center to effect B−O cleavage and the formation of the unusual dihydroborate derivative (213, Figure 21b). 360 Harder and coworkers have recently reported that reaction between compound 113 and the similarly ligated Al(I) derivative, ( Dipp Nacnac)Al (214), resulted in formal oxidative addition of the Mg−H bond to aluminum and production of the Mg−Al-bonded species, [( Dipp Nacnac)Al-(H)-Mg( Dipp Nacnac)] (215) (Figure 21c). 361 In contrast to the outcome of the analogous calcium-centered reaction, which effected catalytic C(sp 2 )−H bond activation (vide infra), compound 215 was found to be stable in refluxing benzene.…”
Section: Stoichiometric and Catalytic Reactivity Of Molecular Magnesi...mentioning
confidence: 99%
“…There has been an increasing interest in Si–N compounds in recent years, as their applications in organic chemistry and materials science have made them indispensable compounds. For instance, polysilazanes are used as precursors in the synthesis of Si–N-based polymers and ceramics and have found applications as ligands in organometallic chemistry. , Due to this versatile use, an easy access to the compounds is of great interest. Established synthesis routes for the formation of Si–N bonds are often complex and produce undesired byproducts. , For example, common reaction routes starting from halosilanes and amines , or metal amides , to give monosilazanes, disilylamines, and diaminosilanes also produce coupling products such as hydrogen halides and metal halide salts that have to be separated from the products.…”
Section: Introductionmentioning
confidence: 99%
“…Established synthesis routes for the formation of Si–N bonds are often complex and produce undesired byproducts. , For example, common reaction routes starting from halosilanes and amines , or metal amides , to give monosilazanes, disilylamines, and diaminosilanes also produce coupling products such as hydrogen halides and metal halide salts that have to be separated from the products. Dehydrocoupling reactions, on the other hand, present a more efficient method for the generation of Si–N bonds that can circumvent these difficulties, as only dihydrogen is produced as a byproduct. , Metal-catalyzed cross-dehydrocoupling reactions of primary or secondary amines with hydridosilanes are therefore of great interest, and many different transition-metal (pre)­catalysts have been developed in the past decade. With recent developments in s-block catalysis, the advantages of alkaline-earth-metal compounds with regard to the high occurrence in the Earth’s crust of these elements and their low toxicities, in particular magnesium and calcium complexes, in amine–silane cross-dehydrocoupling catalysis has been brought into focus. Interestingly, only a handful of magnesium complexes have been employed as catalysts in the cross-dehydrocoupling catalysis of amines and silanes (Figure ). Sadow et al reported the use of a tris­(oxazolinyl)­boratomagnesium complex, I , as a (pre)­catalyst for the formation of Si–N bonds, starting from primary aliphatic and aromatic amines with different silanes, giving high conversions even at room temperature .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation